Two-parameter kinematic theory for punching shear in reinforced concrete slabs with shear reinforcement. (15th February 2019) - Kueres, Dominik; Schmidt, Philipp; Hegger, Josef
Highlights: Development of a kinematic punching theory considering flexural and translational deformations. Development of a novel activation model for the contribution of the shear reinforcement. Validation of the kinematic theory by means of tests with a varying amount of shear reinforcement. Discussion of differences between punching shear behavior of slender and compact slabs. Abstract: Previous investigations prove that the fracture kinematics of reinforced concrete slabs failing in punching are significantly influenced by the slab slenderness. While the deformation behavior of slender slabs is governed by flexural deformations, the behavior of very compact slabs is dominated by translational deformations. In the transition region between slender and very compact slabs, the fracture kinematics at punching failure can be described by both deformation components. Based on the aforementioned results, a two-parameter kinematic theory for punching shear without shear reinforcement was developed. In the theory, a total of four shear contributions (compression ring, aggregate interlock, residual tensile stresses, and dowel action) are considered and the magnitude of the contributions is estimated based on the slab deformations. The evaluation of the theory by means of systematic test series and databanks on both flat slabs and column bases without shear reinforcement revealed good agreement between predictions and experimental results. In this paper, the existing two-parameter kinematic punching theory is extended considering the beneficial effects of shear reinforcement on punching strength. The contribution of the shear reinforcement to the punching strength is determined based on a theoretical model describing the activation of the shear reinforcement depending on the slab deformations and the anchorage quality of the respective shear reinforcement system. The extended theory is validated by means of systematic punching test series on flat slabs and footings with varying amount of shear reinforcement. Further parametric studies are conducted to analyze the punching shear behavior of shear-reinforced concrete slabs in more detail.